Reversal of rice yield decline in a long-term continuous cropping experiment - Dobermann, Achim; Dawe, David; Roetter, Reimund P.; Cassman, Kenneth G. (Wiley, 2000)
In a long‐term continuous cropping experiment at Los Baños, Philippines, three rice (Oryza sativa L.) crops were grown each year with the goals of maximum annual grain production and high N use efficiency. Our objective was to identify the factors responsible for the restoration of yields occurring after 1991. From 1968 to 1991, grain yields declined at an annual rate of 1.4 to 2.0%. From 1991 to 1995, dry season (DS) yields in the highest N treatment increased to within 80 to 100% of the simulated yield potential; yields in the unfertilized control did not increase. Increased solar radiation, increased N rate, and improved timing of N applications accounted for the restoration of yields in the DS. Wet season yields increased in fertilized and unfertilized plots due to greater solar radiation, improved timing of N applications, and increased soil N supply due to dry fallow periods in three years. Residual benefits of soil aeration were short‐term. Reducing preplant N fertilizer and increasing the number of split applications had a greater effect on increasing yield than the increase in the amount of N applied. Our results provide evidence that N deficiency caused the yield decline before 1991. However, the actual processes that caused a decline in soil N supply or plant N uptake remain to be determined. It is possible to sustain high yields and high N use efficiency if fertilizer regimes are updated regularly to maintain the congruence between crop N demand and the N supply from soil and fertilizer.